2018
DOI: 10.1038/s41419-018-0982-2
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and inflammatory bowel disease: a crosstalk between upper and lower digestive tract

Abstract: Helicobacter pylori has coexisted with humans for approximately 60,000 years and greater than 50% of the global population is infected with H. pylori. H. pylori was successfully cultured in vitro in 1983 and studies of H. pylori have achieved substantial advances over the last 35 years. Since then, H. pylori has been characterized as the primary pathogenic factor for chronic gastritis, peptic ulcer, and gastric malignancy. Numerous patients have received H. pylori eradication treatment, but only 1–2% of H. pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 114 publications
(103 reference statements)
2
74
0
4
Order By: Relevance
“…Interestingly, recent studies have elucidated the protective role of H. pylori in an inflamed gut by inducing the expression of Foxp3+ Tregs and suppressing inflammatory cytokines [57]. However, the trade-off between a protective effect in IBD and risk in gastric disease by H. pylori infection is not completely understood [58]. In this study, the supernatants of tested L. rhamnosus strains inhibited the viability of the tested pathogenic indicators (Table 1).…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, recent studies have elucidated the protective role of H. pylori in an inflamed gut by inducing the expression of Foxp3+ Tregs and suppressing inflammatory cytokines [57]. However, the trade-off between a protective effect in IBD and risk in gastric disease by H. pylori infection is not completely understood [58]. In this study, the supernatants of tested L. rhamnosus strains inhibited the viability of the tested pathogenic indicators (Table 1).…”
Section: Discussionmentioning
confidence: 62%
“…45 Indeed, preclinical studies provide evidence that non-pylori enterohepatic Helicobacter species can enhance an IBDlike bowel inflammation. 46 An association between the presence of H pylori in the intestinal mucosa, identified by 16S rRNA gene sequencing, and a UC-like pattern of patients with CD was observed. 47 A pilot study reported that 40% and 56.6% of the histologic samples from the colon of newly diagnosed patients with UC were positive for H pylori by Giemsa and immunohistochemistry staining, respectively.…”
Section: Infl Ammatory Bowel D Is E a S Ementioning
confidence: 90%
“…6 A systematic review evaluated the relationship between H pylori infection and obesity among Chinese adults. The prevalence of H pylori was 42% (95% CI, [37][38][39][40][41][42][43][44][45][46][47] and mean difference of BMI between subjects with and without H pylori infection was 0.94 (95% CI, −0.04 to 1.91). The OR value was 1.20 (95% CI, 1.13-1.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Both Desulfovibrio and Bilophila are conditional pathogens, creating H 2 S in combination with H 2 by sulfuric acid or sulfur-containing compounds, which has an important relationship with the in ammatory state of the intestinal epithelium (such as UC) [42]. Studies have shown that the body with Helicobacter removed is more susceptible to colitis than the untreated group, suggesting that Helicobacter has potential protective effects on colitis patients [43]. Therefore, these result further indicated that the amelioration of UC using SLBZS may be mediated by the enrichment of bene cial bacteria to product SCFA for protection of colon mucosa and a reduction in bacteria, such as Bacteroides, Desulfovibrio and Bilophila, to inhibit in ammation.…”
Section: Discussionmentioning
confidence: 99%